Comparison of air dose and operator exposure from portable X-ray units. (November 2020) - Iwawaki, Atsushi; Otaka, Yusei; Asami, Ruri; Ishii, Takeru; Kito, Shinji; Tamatsu, Yuichi; Aboshi, Hirofumi; Saka, Hideki
Highlights: This study aimed at comparing air dose and operator exposure from X-ray units. It was suggested that using shield was effective for the exposure reduction. Finger dose was low with the NOMAD models, with no significant difference found. Calculation of the limits of radiographed images and bodies. Even if it does not reach the operation limit, stochastic effects can be increased. Abstract: This study was aimed at investigating and comparing exposure dose of workers and the surrounding workers. In addition, worker's exposure was also measure about lens and finger. Four intraoral portable X-ray units were evaluated. The stray radiations were measured using Pitman 37D and ionization chamber (Pitman). MyDosemini (ALOKA) was used for measurement of the finger exposure dose. Without the shield became high in anterior 0.5 m. Comparing the air dose for the four models used in this study showed a high tendency for the two NOMAD models. And using the shields, the images could be taken 4.6 times of the baseline at a maximum and 3.6 times on average. The finger radiation exposure dose was low with both of the NOMAD models, with no significant difference found. By setting the baseline value without a shield, finger radiation exposure when using a shield was lower than the detection limit for the D3000, and was reduced by approximately 94–96% for other three models. All models can photograph around 100 bodies, so it is considered that it is not necessary to switch out the operator considering the operation limit. But even if it does not reach the operation limit, the stochastic effects of radiation exposure can be increased as well as the deterministic effects of the operation limit. The operator and the surrounding workers seek to protect themselves. It is important to perform exposure management that takes into account the stochastic effects to the operator and the surrounding workers.